Production and Characterization of Bioethanol from Straw Waste Through Hydrolysis and Fermentation Processes - Thahir, Muhammad Taufiq; Rina; Husna, Saadatul (Unit Penelitian dan Pengabdian Kepada Masyarakat, AK-Manufaktur Bantaeng, 2024)
Research has been conducted to produce bioethanol from agricultural waste, specifically rice straw, using hydrolysis and fermentation methods. The process stages start from sample preparation, delignification, hydrolysis, fermentation, and purification. The amount of yeast added, and the fermentation time were varied, specifically 2 grams, 4 grams, and 6 grams successively for 3, 5, and 7 days. The results show that ethanol was successfully produced with concentrations ranging from 0.4 to 0.9%. The optimum variation was obtained on the fifth day with the addition of 6 grams of yeast. The obtained ethanol underwent physical characteristic testing including color, odor, viscosity, and density.